2020
DOI: 10.12659/msm.923855
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Clinical and Preclinical Studies on Therapeutic Strategies Using Interleukin-12 in Cancer Therapy and the Protective Role of Interleukin-12 in Hematological Recovery in Chemoradiotherapy

Abstract: Interleukin-12 (IL-12), a heterodimeric glycoprotein with α and β subunits covalently bonded with a disulfide bond, is a potent anticancer agent. Its action is accomplished through a linkage of the adaptive and innate immune responses. IL-12 can promote the recovery of the hematopoietic system after cancer chemoradiotherapy by stimulating the physiological processes of stem cells, including cell proliferation and differentiation, reconstitution of hematopoietic function, and peripheral blood count recovery. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A study revealed (Mehrotra et al, 1993) The clinical application of IL-12 is limited due to its adverse reactions. Some researchers attribute IL-12's systemic toxicity mainly to the induction of IFN-γ (Ding et al, 2021).…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…A study revealed (Mehrotra et al, 1993) The clinical application of IL-12 is limited due to its adverse reactions. Some researchers attribute IL-12's systemic toxicity mainly to the induction of IFN-γ (Ding et al, 2021).…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…IL12 has been extensively applied in the fields of tumor immunotherapy and the prevention or treatment of acute radiation syndrome (Li et al, 2020). However, to conduct further clinical research, it is necessary to follow the relevant guidance principles for nonclinical safety evaluation studies issued by regulatory agencies such as the International Council for Harmonization (ICH), Food and Drug Administration (FDA), or National Medical Products Administration (NMPA) and carry out the work in Good Laboratory Practice (GLP)‐certified laboratories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation